2007
DOI: 10.1504/ijwmc.2007.013791
|View full text |Cite
|
Sign up to set email alerts
|

A security solution for IEEE 802.11's ad hoc mode: password-authentication and group Diffie Hellman key exchange

Abstract: The IEEE 802 standards ease the deployment of networking infrastructures and enable employers to access corporate networks while traveling. These standards provide two modes of communication called infrastructure and ad-hoc modes. A security solution for the IEEE 802.11's infrastructure mode took several years to reach maturity and firmware are still been upgraded, yet a solution for the ad-hoc mode needs to be specified. The present paper is a first attempt in this direction. It leverages the latest developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In [21], researchers proposed a secured password based on authenticated group DiffieHellman protocol, which is wellsuited to authenticate users in the WMNs. Unfortunately, the proposed implementation does not consider the routing protocol in the WMNs.…”
Section: Related Workmentioning
confidence: 99%
“…In [21], researchers proposed a secured password based on authenticated group DiffieHellman protocol, which is wellsuited to authenticate users in the WMNs. Unfortunately, the proposed implementation does not consider the routing protocol in the WMNs.…”
Section: Related Workmentioning
confidence: 99%
“…Bresson et al [4] proposed a static group key exchange protocol which was an authenticated extension of [3].In Bresson et al's subsequent work they extended the static protocol to dynamic case handling addition(merge) and deletion(partition) of group members which is secure under Random Oracle Model(ROM) or standard assumptions .Recently, Bresson et al [5] proposed another static passwordbased group key agreement adoptable in Ad-hoc environment. All protocols mentioned above need more than n rounds communications.…”
Section: A Related Work and Our Contributionmentioning
confidence: 99%
“…More recently, Abdalla et al [3] showed that the 2-party password-based authenticated key exchange protocol in [18] is also secure in the UC model against adaptive adversaries assuming the random-oracle and ideal-cipher models. In the group passwordbased AKE scenario, there has been a few protocols proposed in the literature, from the initial work by Bresson et al [17,19] to the more recent proposals by Dutta and Barua [30], Abdalla et al [1,2,4], and Bohli et al [12]. However, none of them appear to satisfy the security requirements being considered in this paper.…”
Section: Introductionmentioning
confidence: 99%